An Evaluation of Architect Abdul Wahid El-Wakil’s Mosques in Jeddah, Saudi Arabia - Akyıldız, Şeyma (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2021)
• Araştırma Başlığı :- Cidde’deki Abdul-Wahid El-Wakil’in Camilerinin Değerlendirilmesi. • Araştırmacı :- Şeyma Akyıldız. • Araştırma Fikri :- El-wakil’in, orijinal mimari kimliğini bozmadan geçmişin özgünlüğü ile bugünün ve geleceğin modernliği arasında bir köprü oluşturan camilerin incelenmesi. • Hedef :- Yerel malzemelerle modern teknolojiyi kullanarak geleneksel Arap mimarisinin önemini vurgulamada büyük rol oynayan mimari figürlerin incelenmesi. • Araştırma konusu :- Abdul-Wahid Al-wakil mimari tarzını incelemek. • Araştırma Bölümleri:- • Birinci bölüm: Giriş. • İkinci bölüm: Abdul-Wahid El-Wakil’in Biyografisi. • Üçüncü bölüm: Camii Tasarımı. • Dördüncü bölüm: Netice, Sonuçlar ve öneriler. Birinci bölümde, en temel araştırma terminolojisi vurgulanacak, amaçlanan amacı ve faydaları ayrıntılı olarak açıklanacaktır. İkinci bölüm, mimar Abdul Wahid El-Wakil'e bir giriş ve akademik ve kariyerine genel bir bakış, ayrıca dünyanın çeşitli yerlerindeki bazı eserlerinden bahsediyor ve geçmiş ve şimdiki tarzını anlatıyor ve bir analiz içeriyor. El-Wakil'in projelerindeki bazı inşaat mekanizmalarından bazıları. Üçüncü bölüm ise Suudi Arabistan Cidde'deki El-Wakil’in camisinin değerlendirilmesi, planların ve cephe özelliklerinin incelenmesi ve dekorasyon teknikleri ile İnşaat ve Yapı Malzemelerinin analiz edilmesiyle ilgili olacak, ve son olarak dördüncü bölüm çalışmanın sonucu, bulguları ve önerileri. • Sonuçlar ve Öneriler:- Sonuçlar: El-wekil'in tarzı İslam mimarisinin canlanmasına ve İslam mimarisi kavramının gerçek kimliğinin korunmasına katkıda bulundu. Öneriler: İslami kimliğin korunmasında rolü olan mimari figürlere odaklanarak, Arap İslam mimarisine ışık tutuyor ve kendi gelenek değerine odaklanıyorum.

• Research Title:- The Evaluation of Abdul-Wahid El-Wakil’s Mosques in Jeddah. • Researcher :- Şeyma Akyıldız. • Research Idea:- Studying El-wakil's mosques, which form the bridge between the authenticity of the past and the modernity of the present and the future without distorting the original architectural identity. • Goal:- Studying architectural figures who have a major role in highlighting the importance of traditional Arab architecture using local materials with modern technology. • Research Subject:- Studying Abdul-Wahid El-wakil’s architecture style, then Analyze his mosques, and what affected his works. • Research Chapters:- The research will be divided into four chapters. It will be as follows: • Chapter one: Introduction. • Chapter two: Abdul-Wahid El-Wakil’s Biography. • Chapter three: Mosque Design. • Chapter five: Conclusion, Results, and recommendations. In the first chapter, the most main research terminology will be highlighted, With an explanation of its intended purpose and its benefits in detail. The second chapter is an introduction to the architect Abdul Wahid El-Wakil and an overview of his academic and career, also mentioning some of his works in various parts of the world, and describe his style in the past and present, and include an analysis of some of the construction mechanisms in El-Wakil's projects. And the third chapter will be about an evaluation of El-Wakil’s mosque in Jeddah Saudi Arabia, studying the plans and facade features and analyzing decoration techniques and Construction and Building Materials. And finally chapter four the conclusion, findings, and recommendations of the study. • Results and Recommendations:- Results: El-wakil's thought contributed to the revival of Muslim countries' architecture And preserving the true identity of the concept of Arab Islamic architecture. Recommendation: Shed light on Arab Islamic architecture, and focus on its traditional value, by focusing on architectural figures who have a role in preserving the Islamic identity.
Suudi Arabistan, Cidde’deki Abdul Wahid Alwakil’in Camilerinin Değerlendirilmesi
Keywords: Abdul-Wahid El-Wakil; Camii Tasarımı; El-Wakil’in Mimarisi; Korniş Camii; Ruveys Camii; Bin Laden Camii; El Jazira Camii; Kral Suud Camii; Mosque Design; El-Wakil Architecture; The Corniche Mosque; Ruwais Mosque; Bin Ladin Mosque; Island Mosque; King Saud Mosque